Comparative Analysis of the Crime of Cohabitation in the New Criminal Code and Islamic Criminal Law - Saidah, Siti Nur; Mulyaningsih, Eli; Dillah, Muhammad Arya (UNTAG Law Review, 2025)
The amendment to the Criminal Code through Law Number 1 of 2023 includes cohabitation as a new criminal offense in Article 412, which was not previously regulated in the old Criminal Code. This criminalization emerged as an effort to align the law with the social, religious, and moral values of Indonesian society. This study uses a legal-normative method with a qualitative approach, is descriptive-analytical in nature, and uses secondary data through a literature review. In Islamic criminal law, cohabitation is considered an act that is close to adultery, as it violates the prohibition against committing such a vile act. Several opinions from scholars and studies state that cohabitation can be categorized as jarimah zina if sexual relations are proven, and is subject to hadd punishment; however, if not proven, the perpetrator can only be subject to ta'zir. The results of the analysis show that the regulation of cohabitation in the new Criminal Code is not yet fully in line with the principles of Islamic criminal law, especially in terms of evidence and types of punishment.